2021
DOI: 10.1016/j.transproceed.2021.02.015
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Heart Transplant: A Case Series and Review of the Literature

Abstract: COVID19 has resulted in many challenges in patient care especially high-risk populations such as heart transplant patients. Patients with heart transplant experience a significantly higher mortality rate with COVID19 infection, and management is based on extrapolation from clinical trials done on non-transplant patients, and from clinical experience. Here we report four cases of heart transplant patients who presented in late 2020 with COVID19 infection. Patients presented with symptoms similar to those seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 18 publications
1
11
0
7
Order By: Relevance
“…Among 28 cases of COVID‐19, 15 (54%) were admitted to the hospital for closer monitoring (Table 3, Figure 1). The most common presenting symptoms were cough (36%), fevers (25%), gastrointestinal symptoms (25%), shortness of breath (21%), loss of taste/smell (21%), and myalgias (7%), which is similar to the presenting symptoms reported in other studies on HT recipients 1–3,7–11,15–17 and in the general population 12,13 . Atypical symptoms were also quite common (reported in 46% of patients) and included chills, generalized pain and weakness, dizziness, sore throat, altered mental status, chest pain, headache, diffuse tingling, and rhinorrhea.…”
Section: Resultssupporting
confidence: 79%
“…Among 28 cases of COVID‐19, 15 (54%) were admitted to the hospital for closer monitoring (Table 3, Figure 1). The most common presenting symptoms were cough (36%), fevers (25%), gastrointestinal symptoms (25%), shortness of breath (21%), loss of taste/smell (21%), and myalgias (7%), which is similar to the presenting symptoms reported in other studies on HT recipients 1–3,7–11,15–17 and in the general population 12,13 . Atypical symptoms were also quite common (reported in 46% of patients) and included chills, generalized pain and weakness, dizziness, sore throat, altered mental status, chest pain, headache, diffuse tingling, and rhinorrhea.…”
Section: Resultssupporting
confidence: 79%
“…Of the thirty-three studies, eleven were retrospective case series [ 7 , 11 , 14 , 19 , 20 , 26 , 29 33 , 38 , 39 ], while twenty-two were case reports [ 8 – 10 , 12 , 13 , 15 18 , 21 25 , 27 , 28 , 34 – 37 ]. All were peer-reviewed.…”
Section: Resultsmentioning
confidence: 99%
“… Does the case report provide take away lessons? Total score Ahluwalia et al [ 11 ] 100% Ammirati et al [ 12 ] 100% Berg et al [ 28 ] 100% Ballout et al [ 29 ] 100% Bosch et al [ 13 ] X X X X 50% Carraffa et al [ 14 ] 100% ...…”
Section: Methodsmentioning
confidence: 99%
“…A reduction of immunosuppression with supportive treatment, including convalescent plasma, remdesivir, and dexamethasone, resulted in the resolution of her symptoms within days [ 83 ]. Additionally, two heart transplant recipients were successfully treated with a combination of dexamethasone and remdesivir [ 84 ].…”
Section: Therapeutic Options In Sot Recipients In Covid-19mentioning
confidence: 99%
“…A case series of four heart transplant recipients showed that they were successfully treated with dexamethasone (with the addition of remdesivir in two patients) [ 84 ]. In a cohort of 32 lung transplant recipients with moderate/severe COVID-19, the mortality rate was 34%.…”
Section: Therapeutic Options In Sot Recipients In Covid-19mentioning
confidence: 99%